The Fetal Origins of Obesity: Early Origins of Altered Food Intake - S. Muhlhausler, B.; Y. Ong, Z. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2011)
There is now clear evidence from population-based and experimental animal studies that maternal obesity and maternal overnutrition, particularly excessive intake of high-fat and high-sugar diets, is associated with an increased risk of obesity and type 2 diabetes in the offspring. Whilst the physiological reasons for this association are still not fully understood, one of the key pathways appears to be the ability of exposure to an oversupply of energy, fat and sugar during critical windows of development to program an increased food intake in the offspring. This review will focus on our current understanding of the programming of food intake, with a focus on the importance of the maternal diet. Specifically, we will discuss how exposure to an increased energy supply before birth and in early infancy, and/or increased maternal intake of palatable foods alters the development of the systems regulating appetite and food preferences, and how these changes interact to promote excess consumption and thus predispose the offspring to weight gain and obesity.
Keywords: appetite